Development of Augmented Reality as a Learning Media on Informatics Learning Hardware Material in SMP - Vani Aprianto; Munir Munir; Rani Megasari (NUANSA INFORMATIKA, 2025)
This study was motivated by the researcher's concern about the difficulty of informatics subjects at the junior high school level. Moreover, when examined, hardware material is a challenge for teachers and students in carrying out learning in the classroom. In some places, student motivation and learning outcomes in understanding hardware material tend to be low. The purpose of this study is to develop Augmented Reality learning media on learning informatics hardware material in class VII junior high school. The research method used is Research and Development (R&D) which uses the Brog & Gall research model with 10 models, then simplified into 3 major steps which will be implemented in the development procedure process by adopting the results of Sukmadinata's R&D model simplification. Testing the feasibility of development, it was tested with the results of a media expert assessment of 81.25% very feasible criteria. While the material expert assessment with a score of 81.82% is very feasible. The results of the implementation of student respondents on a limited scale were 76.42% of the interesting category and a wide scale of 84.11% of the very interesting category. So it can be concluded through the results of expert validation, limited scale trials and wide scale trials, that augmented reality as learning media is feasible to use as a learning tool during the learning process